Does an undervalued currency merit economic growth?: Evidence from Taiwan - Yan Ho-Don; Yang Cheng-Lang (Panoeconomicus, 2012)
Whether an undervalued currency is an attainable industrial policy for developing countries’ sustained development has recently invoked many discussions. This paper studies the case of Taiwan after first determining the misalignment of Taiwan’s currency by estimating the fundamental equilibrium real exchange rate. Three sub-periods for Taiwan’s currency exchange rate misalignment are identified: undervaluation in the periods 1981-1986 and 1998- 2008 and overvaluation during 1987-1997. Second, we use a vector autoregression (VAR) model to examine the Granger causality between exchange rate misalignment and GDP, by incorporating export and investment variables. The evidence shows that exchange rate misalignment does Granger cause GDP and it mainly comes from the third sub-period when the Taiwan dollar was undervalued. From past experience and the current economic doldrums of the last resort of global exports - the United States - currency undervaluation is not a validated strategy upon which emerging markets can wishfully impinge.